2017
DOI: 10.1016/j.envpol.2016.11.047
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons (PAHs) enriching antibiotic resistance genes (ARGs) in the soils

Abstract: The prevalence of antibiotic resistance genes (ARGs) in modern environment raises an emerging global health concern. In this study, soil samples were collected from three sites in petrochemical plant that represented different pollution levels of polycyclic aromatic hydrocarbons (PAHs). Metagenomic profiling of these soils demonstrated that ARGs in the PAHs-contaminated soils were approximately 15 times more abundant than those in the less-contaminated ones, with Proteobacterial being the preponderant phylum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(44 citation statements)
references
References 69 publications
(81 reference statements)
3
39
0
2
Order By: Relevance
“…Moreover, many microorganisms act as biological control agents by inhibiting the growth of pathogens (Varma and Buscot, 2005). The homeostasis of soil may be disturbed by biotic and abiotic factors, including bacteriophages, predation, competition, pesticide, heavy metals, toxic hydrocarbons, and antibiotics (Cycoń et al, 2011; Cycoń and Piotrowska-Seget, 2015, 2016; Sułowicz and Piotrowska-Seget, 2016; Xu et al, 2016; Chen et al, 2017; Wepking et al, 2017; Orlewska et al, 2018a). The high antimicrobial activity of antibiotics in soil should differentially inhibit the growth of soil microorganisms and thus influence the soil microbial community composition, which may result in alterations of the ecological functionality of the soil (Kotzerke et al, 2008; Keen and Patrick, 2013; Molaei et al, 2017) (Figure 3).…”
Section: Impact Of Antibiotics On Soil Microorganismsmentioning
confidence: 99%
“…Moreover, many microorganisms act as biological control agents by inhibiting the growth of pathogens (Varma and Buscot, 2005). The homeostasis of soil may be disturbed by biotic and abiotic factors, including bacteriophages, predation, competition, pesticide, heavy metals, toxic hydrocarbons, and antibiotics (Cycoń et al, 2011; Cycoń and Piotrowska-Seget, 2015, 2016; Sułowicz and Piotrowska-Seget, 2016; Xu et al, 2016; Chen et al, 2017; Wepking et al, 2017; Orlewska et al, 2018a). The high antimicrobial activity of antibiotics in soil should differentially inhibit the growth of soil microorganisms and thus influence the soil microbial community composition, which may result in alterations of the ecological functionality of the soil (Kotzerke et al, 2008; Keen and Patrick, 2013; Molaei et al, 2017) (Figure 3).…”
Section: Impact Of Antibiotics On Soil Microorganismsmentioning
confidence: 99%
“…Due to difficulties in cultivating sediment micro-organisms (Great Plate Anomaly), it is currently unknown how many types of ARGs exist. However, the development of sequencing-based descriptive metagenomic approaches has provided the means to analyse the occurrence and abundance of previously unrecognised ARGs with examples of |successful applications (Li et al 2015a;Monier et al 2011;Chen et al 2017). The extent that environmental conditions impact antimicrobial resistance is becoming increasingly known.…”
Section: Development Of Antimicrobial Resistancementioning
confidence: 99%
“…Microbial degradation has an important role in the natural attenuation of PAHs in contaminated matrices (Van Dillewijn et al 2009); however, the presence of PAHs changes the community structure of indigenous bacteria with the number of hydrocarbon-degrading bacteria increases with increasing available hydrocarbons (De Menezes et al 2012;Zhang et al 2010;Maila et al 2005); it is difficult to understand which communities are present in historically contaminated sediments (Azarbad et al 2016;Singleton et al 2013). However, many PAH-tolerant bacterial isolates often exhibit strong resistance to metals and antibiotics (Ben Said et al 2008;Máthé et al 2012), and ARGs have been found in PAH-contaminated matrices (Chen et al 2017;Kang et al 2015).…”
Section: Pahs and Amrmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, sublethal concentrations select resistant phenotypes from mutations or horizontal gene transfer (HGT) that sometimes use mobile genetic elements (MGEs) (Kohanski et al, 2010;Baharoglu and Mazel, 2011;Gutierrez et al, 2013;Haaber et al, 2017;Lekunberri et al, 2017). The AR in the environment is a natural process but is also promoted by anthropogenic pollutants like antibiotics, biocides, heavy metals, hydrocarbons, pesticides, and nanomaterials, among others (Baker-Austin et al, 2006;Dealtry et al, 2014;Pal et al, 2015Pal et al, , 2017Chen et al, 2017;Poole, 2017;Wang et al, 2018;Nguyen et al, 2019). Therefore, naturally antibiotic-resistant bacteria (ARB) could be a prime source for antibiotic resistance genes (ARGs) found in pathogens as certain findings may indicate (Rodríguez et al, 2004;Poirel et al, 2005Poirel et al, , 2012Yang J. et al, 2013;Jiang et al, 2017), but may later have evolved and be selected.…”
Section: Introductionmentioning
confidence: 99%